Fast Faraday Cup for Fast Ion Beam TOF Measurements in Deuterium Filled Plasma Focus Device and Correlation with Lee Model - Damideh, Vahid; Ali, Jalil; Saw, S. H.; Rawat, Rajdeep Singh; Lee, Paul; Chaudhary, Kashif Tufail; Rizvi, Zuhaib Haider; Dabagh, Shadab; Ismail, Fairuz Diyana; Lee, Sing (AIP Publishing, 2017)
In this work, the design and construction of a 50 X fast Faraday cup and its results in correlation with the Lee Model Code for fast ion beam and ion time of flight measurements for a Deuterium filled plasma focus device are presented. Fast ion beam properties such as ion flux, fluence, speed, and energy at 2–8 Torr Deuterium are studied. The minimum 34 ns full width at half maximum ion signal at 12 kV, 3 Torr Deuterium in INTI PF was captured by a Faraday cup. The maximum ion energy of 67 6 5 keV at 4 Torr Deuterium was detected by the Faraday cup. Ion time of flight measurements by the Faraday cup show consistent correlation with Lee Code results for Deuterium especially at near to optimum pressures.